The Brachyura (Crustacea: Decapoda) described by Sidney Irving Smith: checklist, dates of publication and bibliography, with a discussion on Xantho stimpsoni A. Milne-Edwards, 1879, and X. stimpsonii Smith, 1869 - Low, Martyn E. Y.; Ng, Peter K. L. (Zootaxa, 2012)
American carcinologist Sidney Irving Smith (1843–1926) established names of one family, seven genera and 50 species ofbrachyuran crustaceans in 11 publications between 1869 and 1885. The precise dates of these publications as determined fromvarious sources are given, with particular emphasis on the relative precedence of four that appeared in 1869. A complete list ofthe brachyuran names proposed by Smith, and their current identities, is also given. Xantho stimpsonii Smith, 1869, a previ-ously overlooked replacement name for Xantho denticulatus Stimpson, 1860 (non White, 1848), is an objective synonym ofWilliamstimpsonia stimpsoni (A. Milne-Edwards, 1873), and the precedence of the two names is reversed to maintain prevail-ing usage of the latter. The same action is also taken for Xantho multidentatus Lockington, 1877, a subjective synonym of Wil-liamstimpsonia stimpsoni (A. Milne-Edwards, 1879). The authorship of the following names previously attributed to attributedto Smith in a publication by Verrill (1869) should be attributed only to the latter author: Hepatella amica (Aethridae), Hypocon-cha panamensis (Dromiidae) and Pinnotheres margarita (Pinnotheridae). Authorship of the name Cardiosoma, an unjustifiedemendation of Cardisoma (Gecarcinidae), is conventionally attributed to Smith (1869) but it was actually first used by Agassiz (1846). Cardisoma is attributed to Latreille, in Latreille, Le Peletier, Serville & Guérin, 1828.